Association of Low Level Viremia with Inflammation and Mortality in HIV-Infected Adults - Eastburn, Abigail (Public Library of Science, 2011)
BACKGROUND: Whether HIV viremia, particularly at low levels is associated with inflammation, increased coagulation, and all-cause mortality is unclear. METHODS: The associations of HIV RNA level with C-reactive protein (CRP), fibrinogen, interleukin (IL)-6 and mortality were evaluated in 1116 HIV-infected participants from the Study of Fat Redistribution and Metabolic Change in HIV infection. HIV RNA level was categorized as undetectable (i.e., “target not detected”), 1–19, 20–399, 400–9999, and ≥10,000 copies/ml. Covariates included demographics, lifestyle, adipose tissue, and HIV-related factors. RESULTS: HIV RNA level had little association with CRP. Categories of HIV RNA below 10,000 copies/ml had similar levels of IL-6 compared with an undetectable HIV RNA level, while HIV RNA ≥10,000 copies/ml was associated with 89% higher IL-6 (p<0.001). This association was attenuated by ∼50% after adjustment for CD4+ cell count. Higher HIV RNA was associated with higher fibrinogen. Compared to an undetectable HIV RNA level, fibrinogen was 0.6%, 1.9%, 4.5%, 4.6%, and 9.4% higher across HIV RNA categories, respectively, and statistically significant at the highest level (p = 0.0002 for HIV RNA ≥10,000 copies/ml). Higher HIV RNA was associated with mortality during follow-up in unadjusted analysis, but showed little association after adjustment for CD4+ cell count and inflammation. CONCLUSION: HIV RNA ≥10,000 copies/ml was associated with higher IL-6 and fibrinogen, but lower levels of viremia appeared similar, and there was little association with CRP. The relationship of HIV RNA with IL-6 was strongly affected by CD4 cell depletion. After adjustment for CD4+ cell count and inflammation, viremia did not appear to be substantially associated with mortality risk over 5 years.